Design and Full-Wave Analysis of Cavity-Backed Resistively Loaded Circular-End Bow-Tie Antennas for GPR Applications – Part I - Caratelli, Diego; Yarovoy, Alexander (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper, the design of cavitybacked bow-tie antennas for ground-penetrating radars is presented. Dielectric embedding and resistive loading of the radiating structure are employed to achieve at least 30 : 1 relative bandwidth (55 MHz? >1.5 GHz), with a maximum antenna size of 40 cm and stable antenna performance over different types of the ground. The design procedure is described in detail and provides useful guidelines for the considered class of radiators. Antenna parameters are optimized numerically to combine a large operational bandwidth with reasonably high antenna efficiency. To this end, a full-wave locally conformal finite-difference time domain procedure useful to model electromagnetic structures having complex geometrical and electrical characteristics in the vicinity of the ground is adopted.